Karakterisasi Sifat Morfologi dan Ketahanan terhadap Penyakit Hawar Daun Bakteri pada Beberapa Varietas Padi - Yuliani, Dini; Wening, Rina Hapsari; Sudir, Sudir (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
Bacterial leaf blight, caused by Xanthomonas oryzae pv oryzae (Xoo) is common disease on rice crop in Indonesia. Resistance variety when available, would be a good control measure to the disease, which could be easily adopted by farmers. Source of gene for resistance needs to be identified among rice genotypes, to be used as parents in the breeding program. This research was aimed to characterize the morphological traits and the degree of resistance among rice genotypes against Xoo pathotype III, IV, and VIII. The experiment was conducted at Sukamandi experimental field of Indonesian Center for Rice Research, during the wet season of 2012/2013 and dry season of 2013, using a randomized factorial design. The first factor was three Xoo pathotypes i.e. pathotype III, IV, and VIII, the second factor was 20 rice genotypes including three check varieties, i.e. Ciherang, Inpari 13, and Angke. Observations of morphological and agronomic characters were done on rice plants started from primordial to grain ripening phase. Observations on BLB disease severity were done by measuring the longest symptoms on the leaves at two, three, and four weeks after inoculation. The morphological characters of the isogenic lines showed moderate leaf surface type with an open habitus (60o). Plant height ranged from 99 to 190 cm, maturity between 109 to 157 days after sowing, and the number of tillers was 9-23 tillers/hill. Against the Xoo pathotype III, IV, and VIII, three genotypes of near isogenic lines i.e. IRBB 60, IRBB 61, and IRBB 55 each was resistance, not significantly different from resistance check variety Angke, in two cropping seasons. All three isogenic lines can be used as parent to develop new resistant variety to bacterial leaf blight.